Evaluasi Perubahan Segmentasi Kinerja Keuangan PT. KB Bukopin, TBK Sebelum dan Sesudah Akuisisi dengan Metode K-Means Clustering - Riri Yunita; Jerry Heikal (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2024)
This study aims to evaluate changes in the segmentation of PT KB Bukopin Tbk's financial performance before and after Kookmin Bank's acquisition. This study uses the K-means clustering method using secondary data in the form of financial data taken from the official website of the Indonesia Stock Exchange, IDX.co.id. The results of the k-means analysis showed that the change in BBKP segmentation from Category 4 (cluster E) in 2019 to Category 3 (cluster C) in 2023 showed significant changes in the company's financial stability and capital adequacy. This research reveals that post-acquisition strategies and policies have successfully made a substantial impact on BBKP's financial structure, as evidenced by a positive increase in the solvency ratio (DER) and capital adequacy ratio (CAR). However, the decline in return on assets (ROA) indicates that operational efficiency is required to improve profitability. The results of the comprehensive and ongoing evaluation show how important it is to thoroughly understand the impact of acquisition activities in the banking industry.